O Zumbo: Um problema de “Direitos Históricos” na delimitação da fronteira - Sampaio, Cristina (Africana Studia, 2020)
The sedimentation of the Portuguese presence along the Zambezi until the Zumbo since the XVIth century, had constitute a unmistakable sign in the colonial frontier’s outline made by the European diplomacy in the ending of the XIXth century, beginning of the XXth century. This text is about the historical antecedents that flowed into the frontier’s delimitation of Zumbo – Tete defined by Portuguese-British treaty, of 1891, and also about the events who had been in the origin of the ground frontier’s demarcation until the nomination of Portuguese and English missions.